Integration and differentiation of self through reminiscing and narrative. Issue 4 (15th August 2019) - Fivush, Robyn
Abstract: Humans construct coherence and meaning in their lives through reminiscing with and about others. The four articles in this Social Development Quartet focus on how reminiscing about emotionally and morally challenging personal experiences is a critical mechanism for integration and differentiation across development, both within the individual and within sociocultural interactions. Examining linguistic forms, emotional disclosure, expressions of perspective, and personal growth, these studies demonstrate that the ways in which we reminisce about our personal past with others matter for developmental outcome. Both the ways in which individuals differentiate between self and other, and between different types of events, and the ways in which individuals integrate perspectives across different types of events is related to emotional well‐being.